2022
DOI: 10.3390/app12146889
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genomic Regions Associated with Fusarium Wilt Resistance in Cowpea

Abstract: Fusarium wilt (FW), caused by the soil-borne fungal pathogen Fusarium oxysporum f. sp. Tracheiphilum, is a serious threat to cowpea production worldwide. Understanding the genetic architecture of FW resistance is a prerequisite to combatting this disease and developing FW resistance varieties. In the current study, a genetic diversity panel of 99 cowpea accessions was collected, and they were infected by a single strain, FW-HZ. The disease index (DI) based on the two indicators of leaf damage (LFD) and vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Fusarium oxysporum is a common soil-borne fungal plant pathogen that infects a wide range of host plants, including cowpea [ 13 , 14 ]. F. oxysporum infects cowpea roots and destroys the vascular cells, inhibiting growth and productivity, with yield losses reaching 70% [ 15 , 16 , 17 ]. Chemical fungicides are most often used to control this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium oxysporum is a common soil-borne fungal plant pathogen that infects a wide range of host plants, including cowpea [ 13 , 14 ]. F. oxysporum infects cowpea roots and destroys the vascular cells, inhibiting growth and productivity, with yield losses reaching 70% [ 15 , 16 , 17 ]. Chemical fungicides are most often used to control this disease.…”
Section: Introductionmentioning
confidence: 99%
“…GWA for Fusarium wilt resistance has been reported in many crop plants. Dong et al (2022) also identified 3 and 7 SNPs significantly associated with LFD and VD in response to Fusarium wilt in cowpea, respectively, on chromosomes 3, 4, 5, 6, and 9. Thirty candidate genes were identified, including leucine-rich repeat protein kinase family proteins, protein kinase superfamily proteins, and zinc finger family proteins.…”
Section: Association Analysis For Fusarium Wilt Resistancementioning
confidence: 85%
“…This powerful approach allows the detection of genes/quantitative trait loci (QTLs) controlling complex traits, and tightly linked markers can be developed for markerassisted selection (MAS). However, successful GWA for Fusarium wilt resistance has been reported in many crop plants, such as cowpea (Dong et al 2022), castor bean (Shaw et al 2022), sweet basil (Gonda et al 2022), strawberry (Pincot et al 2018), cape gooseberry (Osorio-Guarín et al 2016), cotton (Mei et al 2014), pigeon pea (Patil et al 2017), and bottle gourd (Li et al 2021), but not in tomatoes. Therefore, this study aims to identify SNP markers linked to Fusarium wilt resistance in the natural germplasm of tomatoes using the genome-wide association approach.…”
Section: Introductionmentioning
confidence: 99%
“…The BP neural network-based constrained optimization method is a new approach for the optimization of black box problems and includes single-objective optimization methods and multiobjective optimization methods (Dong et al, 2021;Wang et al, 2017;Dong et al, 2018a;Dong et al, 2019). The proposed method is based on the principle of iterative optimization via mathematical programming methods and the functional relationship fitting of BP neural networks.…”
Section: Introductionmentioning
confidence: 99%